Retinoblastoma: childhood cancer - Manrique Arizmendi, Olga Vanessa; Manrique Abril, Fred Gustavo; Bernal-Gomez, Bibiana Matilde (Subcomité editorial y de evaluación de obras de la Facultad de Ciencias de la Salud Editora Revista Dra. Bibiana Matilde Bernal Gómez, 2021)
ABSTRACT The retinoblastoma is a type of pediatric cancer that affects main tissues of the retina of the eye. It arises in the layer of woven nervous rear to the eye wich detects the light of the outside and sends the signals to the brain. It is an intraocular tumor common in children with incidence of 1 for every 15000 children born alive and the second  intraocular tumor more frequent. This type of cancer is developed since embryo and It is often diagnosed at 18 months. This type of cancer could begin since fetal age during pregnancy and at newborn or fist year of  growth. Some studies on this cancer had classified the type according their location, or their oncological status. It should be mentioned the genetic risk, the type of treatment used in some cases, as well one study from Colombia, where three new mutations in the RB1 gene were identified.